Swimming flume for Otago University - Britton, R.; Rogers, N.; Reimann, P. (IPENZ Transactions, 1998)
The University of Otago has incorporated a swimming flume within one of its buildings at the School of Physical Education. This has taken the form of a pumped circulating water channel with variable water speed and temperature control. The purpose of this paper is to describe the challenges offered by the hydraulic, structural and electrical/mechanical aspects of the design and how these were overcome.